Augmented Reality and Virtual Reality New trends in immersive technology - tom Dieck, M.C.; Jung, T.; Loureiro, S. M. C. (2021)
The sixth International Augmented and Virtual Reality conference was held online for the first time. For all of us, 2020 has been a challenging year with many unknowns and changes to the way we work, socialise and operate. “Online” has become the new normal for meetings and conferences, possibly and most likely changing our future behaviours towards a blended online and offline approach. Immersive technologies will become more important and prominent and this collection of papers highlights this trend, implications and future research directions. We hope it offers valuable insights and provides us with ideas and solutions for a future in healthcare, art, tourism, storytelling, marketing and retail, architecture, industrial settings and education.